2018
DOI: 10.5603/kp.a2018.0071
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and cardiovascular disease: new insights

Abstract: The role of oxidative stress in the onset and progression of atherosclerosis and its impact on the development of cardiovascular events has been widely described. Thus, increased oxidative stress has been described in several atherosclerotic risk factors, such as hypertension, dyslipidaemia, peripheral artery disease, metabolic syndrome, diabetes, and obesity. Among others, specific oxidative pathways involving both pro-oxidant and antioxidant enzymes seem to play a major role in the production of reactive oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
141
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(145 citation statements)
references
References 101 publications
(119 reference statements)
1
141
0
3
Order By: Relevance
“…CA, cinnamaldehyde; HO-1, heme oxygenase-1; ICAM-1, intercellular adhesion molecule 1; VCAM-1, vascular cell adhesion molecule 1; TNF-α, tumor necrosis factor α. through simple diffusion or facilitated diffusion by aquaporins (26,27). As ROS are an important risk factor for the development of cardiovascular disease, antioxidant therapies that scavenge ROS are considered an effective strategy for anti-atherosclerotic treatment (5,6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CA, cinnamaldehyde; HO-1, heme oxygenase-1; ICAM-1, intercellular adhesion molecule 1; VCAM-1, vascular cell adhesion molecule 1; TNF-α, tumor necrosis factor α. through simple diffusion or facilitated diffusion by aquaporins (26,27). As ROS are an important risk factor for the development of cardiovascular disease, antioxidant therapies that scavenge ROS are considered an effective strategy for anti-atherosclerotic treatment (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that excessive ROS generation leads to the peroxidation of membrane lipids, disturbs cellular antioxidant signaling and induces apoptosis (4). ROS also play critical roles as pathogenic factors in the development of cardiovascular disease by promoting the apoptosis of endothelial cells (5,6). Therefore, protecting endothelial cells from apoptosis induced by oxidative stress appears to be an effective strategy for the prevention and treatment of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory factors created by macrophages expand the local inflammatory reaction, aggravating AS . In addition, the role of oxidative stress in the progression of AS has been widely focused on . The exploration of the mechanism involved in oxidized low‐density lipoprotein (ox‐LDL)‐induced macrophage inflammation and oxidative stress is becoming increasingly important.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in LDL-C may be due to a decrease in the potential for LDL-C to be removed from the thrombocytopenic cells or liver cells or due to a defect in the apoB100 synthesis on the surface of the LDL particle or its receptors on the surface of hepatocytes and phagocytes [45,46]. As shown in Tables (1) and 2, the activity of Clutathione Peroxidase was significantly reduced (P ≤0.01) in serum cardiovascular patients for both males and females, and Clutathione Pyroxidase is an important enzyme that contributes to the removal of free radical Which are usually associated with vascular disease due to high oxidative stress and this affects the effectiveness of the enzyme that reduces these negative effects [47,48]. The high oxidative stress and the low activity of clutathione peroxidase is attributable to Ench The level of the nuclear factor erythroid 2-related factor 2 (Nrf2), which is responsible for regulating the cloning of genes responsible for the synthesis of protein-based antioxidants, scavenger receptors, and ATP-binding cassett transporters, the Nrf2 factor is directly related to controlling the levels of components that contribute to the process of oxidation and reduction in the body, including Clutathione Peroxidase.…”
Section: Resultsmentioning
confidence: 94%